"Hammering in the wedges": The political praxis of Harriette Colenso in Zululand and Natal, 1884 to 1913 - Gumede, Sizakele (Department of Historical Studies, 2024)
This dissertation tracks and analyses the praxis of the political actor, Harriette Colenso, in support of Africans in the struggle against imperialism, in Natal and Zululand, between 1884 and 1913. It examines the interplay between Colenso's political praxis and the rapidly changing colonial political contexts in which she operates, scrutinising her participation in the developing colonial political order, and looks at the ways in which her political activity imaginatively challenged its boundaries. It argues that she thwarted successive colonial governments' attempts to obliterate the Zulu royal house and the institution of Zulu kingship. With the Zulu already under British subjugation, Colenso was not engaging with the big political questions so much as she was concerned with safeguarding King Dinuzulu and preventing the Usuthu's political situation from worsening. She achieved this by continually countering the colonial governments' political activities, which this study refers to as her ‘hammering in the wedges.' The study shows that she had a series of small successes that in the long-term contributed in important ways to political gains by the Zulu monarchy. The study highlights the characteristic features of Colenso's political praxis, particularly her activity and success in driving wedges between the colonial and imperial officials and authorities. This dissertation is the first scholarly work to examine Colenso's entire active public political life. It also reviews and offers re-interpretations of aspects of her life dealt with in prior scholarship. Its novelty lies in the centring of Colenso as a political actor in her own right, rather than, as is the case in the study by Jeff Guy, using her as a lens on larger political affairs. It augments this innovative perspective with research based on previously untapped archives, offering a fresh look at its subject and hoping to stimulate further research.